Effects of selective logging on advanced regeneration of timber species in the Asenanyo river forest reserve, Ghana - Boateng, Enoch Owusu (2016)
A thesis submitted to the Department of Theoretical and Applied Biology in partial fulfillment of the requirement for the award of the Master of Science degree in Environmental Science.